2022
DOI: 10.1149/1945-7111/ac9d6b
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Oxygen Dissolved in the Liquid Electrolyte on Lithium Metal Anodes

Abstract: Due to the need for high-energy-density storage, Li-O2 batteries and Li metal anodes (LMA) are a focus of extensive research. As safe operation of the LMA is yet not possible, more knowledge about factors influencing the stability of the solid electrolyte interphase (SEI) is necessary to utilize the LMA. Especially concerning the influence of O2 dissolved in the electrolyte, there are still many unanswered questions, and there are conflicting opinions reported. Here, plating/stripping experiments were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…It is likely that also a contribution from Li 2 SO 3 is present, as a result of LiTFSI degradation, in agreement with previous findings. 43 The EDX elemental analysis reported in Table 2 indicates high quantities of sulfur and fluorine, confirming the predominance of LiTFSI fragments in SEI composition. Overall, the effect of DMSO solvation on LiI redox mediation has a detrimental impact on the stability of cell changes occur in the G4 solution.…”
Section: ■ Introductionmentioning
confidence: 57%
“…It is likely that also a contribution from Li 2 SO 3 is present, as a result of LiTFSI degradation, in agreement with previous findings. 43 The EDX elemental analysis reported in Table 2 indicates high quantities of sulfur and fluorine, confirming the predominance of LiTFSI fragments in SEI composition. Overall, the effect of DMSO solvation on LiI redox mediation has a detrimental impact on the stability of cell changes occur in the G4 solution.…”
Section: ■ Introductionmentioning
confidence: 57%
“…Conversely, some other works reported that the SEI layer is more stable in the oxygenated electrolyte than the pristine electrolyte. [ 20–23 ] For instance, Zhou et al. [ 23 ] and Haas et al.…”
Section: Introductionmentioning
confidence: 99%
“…[ 23 ] and Haas et al. [ 20 ] reported that the oxygen can preferentially react with LMA to form an inorganic‐rich SEI layer (e.g., Li 2 O, Li 2 O 2 , and Li 2 CO 3 ), to prevent the further degradation of LMA. Grey et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 3D-F [39,40], oxide, hydroxide and others. All 338 three alloy passivation layers consist of a combination 339 of magnesium oxide and lithium compounds, but the 340 relative fractions vary.…”
mentioning
confidence: 99%